THE EFFECT OF PROBIOTICS ON INSULIN SENSITIVITY, GLYCEMIC CONTROL AND LIPID PROFILE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Lafl, Zin Myo; Ko , Ko; Lafl, Tint Swe; Aung, Moe Wint; Aye, Than Than (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Fermented kimchi, a traditional Korean food, which contains multi-strained probiotics (Innolac) is purported to have beneficial effects on glucose and lipid metabolism in patients with prediabetes and obesity. However, the effect of probiotics in patients with type 2 diabetes remains unclear. This study investigated the effect of probiotics on insulin sensitivity, glycemic control and lipid profile in patients with type 2 diabetes mellitus. METHODOLOGY This was a hospital-based, randomized controlled clinical study conducted in patients consulting at the diabetes clinic of North Okkalapa General and Teaching Hospital during January 2019 to October 2020. A total of 75 patients with HbA1c 7.0% to 8.0% were recruited and prospectively randomized. Eleven patients (14.6% of study population) dropped out, and 32 patients in each group were studied to receive either oral probiotics sachet daily (probiotics group n = 32) or usual medical care (control group n=32) for two months. Determination of HOMA-IR, HbA1c and fasting lipid profile (TC, HDL, LDL and TG) was done at baseline and after 2 months. Mean changes between both groups were compared and analyzed by per protocol analysis. RESULTS There was no significant difference in baseline clinical characteristics between the two groups. The probiotics group showed significant improvement of fasting insulin (-4.26 ± 1.87 mU/L reduction, P=0.02, 95% CI), insulin sensitivity (-1.53 ± 0.67 HOMA IR reduction, P=0.02, 95% CI) and TG level (-25.65 ± 9.68 mg/dl, P=0.01, 95% CI) compared with the control group. There was no significant improvement of glycemic control (FBG and HbA1c), TC, HDL and LDL in the probiotics group compared with the control group. No significant adverse event was seen in both groups. CONCLUSIONS In patients with inadequately controlled type 2 diabetes mellitus, supplementation of probiotics revealed improvement in insulin sensitivity (HOMA-IR), fasting insulin and triglyceride (TG) but did not show improvement in FBG, HbA1C and lipid profile (TC, HDL and LDL).